Label-free quantitative measurement of cardiovascular dynamics in a zebrafish embryo using frequency-comb-referenced-quantitative phase imaging - Boonruangkan, Jeeranan (SPIE-Intl Soc Optical Eng, 2023)
10.1117/1.jbo.26.11.116004